2000
DOI: 10.1111/j.1440-1711.2000.t01-3-.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Tamm‐Horsfall protein to complement 1q measured by ELISA and resonant mirror biosensor techniques under various ionic‐strength conditions

Abstract: The purpose of the present study was to quantify the binding affinity between Tamm-Horsfall protein (THP) and complement 1q (C1q) using ELISA and a resonant mirror biosensor. In ELISA, immobilized THP was incubated with soluble C1q under both low and physiological ionic-strength conditions. Tamm-Horsfall protein bound C1q with an equilibrium dissociation constant (KD) of 1.9 +/- 0.6 nmol/L in low ionic-strength Tris buffers (20 mmol/L NaCl, pH 7.5) and with a lower affinity (KD of 13.4 +/- 4.7 nmol/L) in physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…However, Moonen et al [37] reported that THP could not bind with native cytokines including TNF-α. In addition, the binding of THP to complement 1 and complement 1q depends on the electrostatic evens as demonstrated by the influence of hydrogen concentration and ionic-strength on THP-C1q binding affinity [16,38]. In this study, we found that enzymatic digestion of THP with neuraminidase or β-galactosidase did not significantly affect the binding activity with different protein molecules, although a tendency of decrease was shown in Figs.…”
Section: Discussioncontrasting
confidence: 42%
“…However, Moonen et al [37] reported that THP could not bind with native cytokines including TNF-α. In addition, the binding of THP to complement 1 and complement 1q depends on the electrostatic evens as demonstrated by the influence of hydrogen concentration and ionic-strength on THP-C1q binding affinity [16,38]. In this study, we found that enzymatic digestion of THP with neuraminidase or β-galactosidase did not significantly affect the binding activity with different protein molecules, although a tendency of decrease was shown in Figs.…”
Section: Discussioncontrasting
confidence: 42%
“…At 1:10 urine dilution, the optimum WGA concentration for plate coating was found to be 10 μg/mL, where binding of urinary THP to WGA was a linear function from 1 – 10 μg/mL WGA, increasing in WGA concentration after 10 μg/mL does not improve the OD of the assay. Bovine serum albumin (BSA) was used to block the non-lectin binding sites on the plate since THP does not bind to BSA 19. The WGA microtiter plates were sealed and stored at 4 o C where they were stable for at least 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…C1q recognizes several charged molecules, including IgG (22), IgM (23), spectrin (24), OmpK36 (25), Tamm-Horsfall protein (26), decorin (27), and fibromodulin (28). Many of these interactions have been shown to be sensitive to the ionic strength of the binding buffer.…”
Section: Binding Of C1q To Igg1 Crp and Ptx3 Is Highly Electrostatimentioning
confidence: 99%